Functional subdomains of STAT2 required for preassociation with the alpha interferon receptor and for signaling. - Li, X (1997)
Two members of the STAT signal transducer and activator of transcription family, STAT1 and STAT2, are rapidly phosphorylated on tyrosine in response to alpha interferon (IFN-alpha). Previous work showed that in the mutant human cell line U6A, which lacks STAT2 and is completely defective in IFN-alpha signaling, the phosphorylation of STAT1 is very weak, revealing that activation of STAT1 depends on STAT2. We now find that STAT2 binds to the cytoplasmic domain of the IFNAR2c (also known as IFNAR2-2) subunit of the IFN-alpha receptor in extracts of untreated cells. STAT1 also binds but only when STAT2 is present. The activities of chimeric STAT2-STAT1 proteins were assayed in U6A cells to define regions required for IFN-alpha signaling. Previous work showed that a point mutation in the Src homology 2 (SH2) domain prevents STAT2 from binding to phosphotyrosine 466 of the IFNAR1 subunit of the activated receptor. However, we now find that the entire SH2 domain of STAT2 can be replaced by that of STAT1 without loss of function, revealing that other regions of STAT2 are required for its specific interaction with the receptor. A chimeric protein, in which the N-terminal third of STAT2 has replaced the corresponding region of STAT1, did preassociate with the IFNAR2c subunit of the receptor, became phosphorylated when IFN-alpha was added, and supported the phosphorylation of endogenous STAT1. These results are consistent with a model in which STAT2 and STAT1 are prebound to the IFNAR2c subunit of the resting receptor. Upon activation, the IFNAR1 subunit is phosphorylated on Tyr-466, allowing the SH2 domain of STAT2 to bind to it; this is followed by the sequential phosphorylation of STAT2 and STAT1.